Using the Washoe Language to Inform Hydrologic and Environmental Models. Issue 5 (14th August 2017) - Fillmore, Helen
Abstract : Article impact statement : Listening to indigenous stakeholders, in their language, can improve the quality and impact of hydrologic and environmental models.